Marine tourism, climate change, and resilience in the Caribbean. - Ettenger, Kreg, (Tourism and hospitality management collection., 2018)
As the nations of the Caribbean respond to the emerging effects of climate change and prepare for those to come, tourism has the potential to either worsen or mitigate these impacts. In the four volumes of this collection, we look at the role of coastal and marine tourism in the Caribbean and similar regions, considering the impacts of the tourism sector on marine and coastal environments, and on the human communities that depend on them. We also explore the way the tourism industry is responding to climate change, and how various sectors are adapting and preparing for various types of impacts. Through essays and case studies by scientists, business leaders, government and NGO staff, and others, we show that tourism could lead the way in reducing human-induced climate impacts, protecting and restoring crucial ecosystems and habitats, and building sustainable futures for the people of the Caribbean and beyond. In this book, the last of four total volumes on coastal tourism and marine tourism, we look specifically at marine recreation and how its various sectors--ranging from surfing, diving and sport fishing, to yachting and cruise ships--are coping with and preparing for climate change in the Caribbean. As with the other three volumes, we focus on examples that show how industry leaders are responding to climate change, using their power and resources to foster positive change in the Caribbean and other parts of the world.